Modern-ocean ground-truthing of planktic foraminifer nitrogen isotopes : a proxy for surface ocean nutrient conditions - Smart, Sandi M. (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.